Oral Alterations in Diabetes Mellitus - Cicmil Smiljka; Mladenović Irena; Krunić Jelena; Ivanović Dragan; Stojanović Nikola (Balkan Stomatological Society, 2018)
Diabetes mellitus is one of the most common chronic diseases which continue to increase in number and significance. It presents the third most prevalent condition among medically compromised patients referring for dental treatment. Diabetes mellitus has been defined as a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Hyperglycemia leads to widespread multisystem damage which has an effect on oral tissue. The present article summarizes current knowledge regarding the association between diabetes mellitus and oral and dental health.